IMPLEMENTATION OF SUSTAINABLE PROCUREMENT: A CASE STUDY OF AN INTERNATIONAL CHAIN HOTEL - Nyoman Berlian, Ida Ayu; Mareni, Ni Ketut; Rukmiyati, Ni Made Sri (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study aims to evaluate the implementation of sustainable/friendly procurement in International Chain Hotels/Hotel X. This research is a descriptive qualitative research using 2 informants. Data collection was carried out by interview, observation and documentation study. The analysis techniques used are data reduction, data presentation, and conclusion drawing. The results showed that six of the ten Hotel X indicators were successfully implemented, while four indicators had not been implemented due to obstacles. The constraints faced include gradual implementation, limited sustainable local suppliers, low demand from operations, absence of warehouses (direct cost), limited availability and choice. This research provides valuable insights to improve socially and environmentally responsible sourcing practices in the hospitality sector, paving the way for wider industry adoption and long-term sustainability. By understanding the constraints and challenges, hospitality organizations can formulate more effective strategies for implementing sustainable procurement, ultimately improving corporate image and customer satisfaction, and contributing to environmental sustainability.